A Major Facilitator Superfamily Peptide Transporter From Fusarium oxysporum Influences Bioethanol Production From Lignocellulosic Material - Nugent, Brian; Ali, Shahin S.; Mullins, Ewen; Doohan, Fiona M. (Frontiers in Microbiology, 2019)
Fusarium oxysporum is a leading microbial agent in the emerging consolidated bioprocessing (CBP) industry owing to its capability to infiltrate the plant’s lignin barrier and degrade complex carbohydrates to value-added chemicals such as bioethanol in a single step. Membrane transport of nutrients is a key factor in successful microbial colonisation of host tissue. This study assessed the impact of a peptide transporter on F. oxysporum’s ability to convert lignocellulosic straw to ethanol. We characterized a novel F. oxysporum peptide transporter (FoPTR2) of the dipeptide/tripeptide transporter (PTR) class. FoPTR2 represents a novel transporter with high homology to the Trichoderma sp. peptide transporters ThPTR2 and TrEST-AO793. Its expression level was highly activated in nitrogen-poor environments, which is a characteristic of PTR class peptide transporters. Overexpression and post-translational gene silencing of the FoPTR2 in F. oxysporum affected the peptide transport capacity and ethanol yielded from a both a wheat straw/bran mix and glucose. Thus, we conclude that it FoPTR2 plays a role in the nutrient acquisition system of F. oxysporum which serves to not only enhance fungal fitness but also CBP efficacy.